Design of sustainable cattle production with base of silvopastoril systems to improve the animal production and to achieve the environmental sustainable - Jiménez Trujillo, J.A. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),